2015
DOI: 10.17531/ein.2015.4.20
|View full text |Cite
|
Sign up to set email alerts
|

A numerical-experimental study on damaged beams dynamics

Abstract: Article citation info: IntroductionIn many contemporary structures various types of defects can appear leading to significant reduction of the element rigidity and changing its overall mechanical behaviour. A special challenge is detection and localization of hidden defects, which can have many forms depending on the scale of the problem, eg. dislocations, voids or inclusions in microscale [43,49,44,3] to macroscopic defects, such as delamination in laminated composites [31] or welds in metallic materials [53,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…The aim of numerical analysis was to predict strength of material and to shorten the time needed for experimental material testing. The numerical study shown to be very reliable for some similar testings such as welded joints [11], bucket wheel boom hoist system [12], some composite materials [13] or even transmission gears [14] and beams [15]. Also, some interesting findings on this steel can be found in research of properties of HSS S690 at low temperatures [16].…”
mentioning
confidence: 65%
“…The aim of numerical analysis was to predict strength of material and to shorten the time needed for experimental material testing. The numerical study shown to be very reliable for some similar testings such as welded joints [11], bucket wheel boom hoist system [12], some composite materials [13] or even transmission gears [14] and beams [15]. Also, some interesting findings on this steel can be found in research of properties of HSS S690 at low temperatures [16].…”
mentioning
confidence: 65%
“…Marwan et al [22] demonstrated that RP contains relevant information about a dynamic system and verified that RP is a sensitive tool in complex systems. Samborski et al [23] proposed a damage identification method based on frequency analysis and RPs, which is numerically verified based on cantilever, simply supported, and doubly clamped beams. Nevertheless, due to the difficulty of getting the sample sets of all kinds of damage in bridges, it is rarely to analyze and detect the bridge damages according to the RPs.…”
Section: Introductionmentioning
confidence: 99%